Essential oil of Melaleuca alternifolia for the treatment of oral candidiasis induced in an immunosuppressed mouse model - Rasteiro, Vanessa Maria de Campos [UNESP]; Costa, Anna Carolina Borges Pereira da [UNESP]; Araújo, Cássia Fernandes [UNESP]; Barros, Patrícia Pimentel de [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Anbinder, Ana Lia [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (BioMed Central LTD, 2014)
The search for alternative therapies for oral candidiasis is a necessity and the use of medicinal plants seems to be one of the promising solutions. The objective of this study was to evaluate the in vitro and in vivo effects of the essential oil of Melaleuca alternifolia on Candida albicans. The minimum inhibitory concentration (MIC) and minimum biofilm eradication concentration (MBEC) of M. alternifolia were determined by the broth microdilution assay. For the in vivo study, twelve immunosuppressed mice with buccal candidiasis received topical applications of M. alternifolia with MBEC. After treatment, yeasts were recovered from the mice and quantified (CFU/mL). Mice were killed for morphologic analysis of the tongue dorsum by optical and scanning electron microscopy. Data were analyzed using Student's t test or Mann-Whitney test. The MIC of M. alternifolia was 0.195% and the MBEC was 12.5%. Treatment with M. alternifolia achieved a 5.33 log reduction in C. albicans and reduced the microscopic lesions of candidiasis. M. alternifolia oil at a 12.5% was effective to eradicate a C. albicans biofilm formed in vitro and to reduce yeasts of C. albicans in an immunosuppressed mouse model.
Keywords: Melaleuca alternifolia; Candida albicans; Oral candidiasis; Murine model